2021
DOI: 10.1111/joac.12407
|View full text |Cite
|
Sign up to set email alerts
|

Intermediary trading and the transformation of marketplaces in Papua New Guinea

Abstract: Trade in marketplaces is central to the domestic distribution of food and other goods throughout the developing world. The commodity networks involved are often complex with numerous intermediate transactions between producer and consumer. By contrast, in the Pacific nation of Papua New Guinea (PNG), marketplace trade has historically occurred through very short commodity networks. This article examines the appearance and growing significance of intermediary trading in PNG's marketplaces and associated trade n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…This is in part because men want the excitement of travel for themselves, but also because they are concerned about the safety of their wives, sisters, and daughters while travelling and overnighting in town (see Chang & Be’Soer, 2011). A similar gradient of male involvement is also evident for betel nut trading, with the large‐scale, long‐distance, and more remunerative wholesale trading role dominated by men, while the small‐scale marketplace‐based wholesaling is dominated by women (Sharp, 2021, p. 540). In Kimbe and Kokopo in 2015, men were also more likely to be involved in reselling (though this was also associated with the commodity traded—mostly betel nut and store goods).…”
Section: Changes In Papua New Guinean Marketplacesmentioning
confidence: 82%
“…This is in part because men want the excitement of travel for themselves, but also because they are concerned about the safety of their wives, sisters, and daughters while travelling and overnighting in town (see Chang & Be’Soer, 2011). A similar gradient of male involvement is also evident for betel nut trading, with the large‐scale, long‐distance, and more remunerative wholesale trading role dominated by men, while the small‐scale marketplace‐based wholesaling is dominated by women (Sharp, 2021, p. 540). In Kimbe and Kokopo in 2015, men were also more likely to be involved in reselling (though this was also associated with the commodity traded—mostly betel nut and store goods).…”
Section: Changes In Papua New Guinean Marketplacesmentioning
confidence: 82%
“…However, these marketing channels occur more frequently in municipalities located on the margins of major state and federal highways, restricting the participation of farmers from more remote municipalities. Although they occur in many municipalities, long channels centered on the figure of the middleman present a very low participation of family farmers, demonstrating the need for the productive specialization of farmers and an improvement in the coordination of chains [31].…”
Section: Discussionmentioning
confidence: 99%
“…This process was necessary to dynamize the mercantile food exchange processes and productive specialization and reduce transaction costs for family farmers. On the other hand, it reduced the earnings of some farmers and excluded others from participating in city fresh food markets [31].…”
Section: Family Farmers In Long Channels: Lessons and Experiences Fro...mentioning
confidence: 99%
“…By 1996, urban rice consumption averaged 66 kg of rice per person annually (Gibson, 2001a). A devaluation of the Kina in 1994 and again in 1998 saw the cost of the predominately imported rice increase significantly, making local fresh produce relatively more affordable (Mellor, 2010;Sharp, 2021). Consequently, research from 2009/2010 found urban households were consuming 59.2 kg per person annually, down from its peak in 1996 (Schmidt et al, 2021).…”
Section: Urban Diets In Port Moresbymentioning
confidence: 99%
“…Although the division of offering meant fresh produce marketplaces focused initially on the sale of fresh local produce, urban markets now offer a growing range of "store goods", which includes items like rice, confectionery, cigarettes and mobile phone credit (Sharp, 2021). Rice is now sold in small 1 to 2 kg bags, but as a relatively new option, most consumers still buy fresh produce from open markets and perishable staples from either small or large supermarkets.…”
Section: Urban Retailing For Staple Foods In Port Moresbymentioning
confidence: 99%